HUBUNGAN BERAT BADAN LAHIR RENDAH DENGAN KEJADIAN STUNTING PADA ANAK USIA 1-5 TAHUN DI WILAYAH KERJA PUSKESMAS JORONGAN: The Relationship Between Low Birth Weight and the Incidence of Stunting in Children Aged 1-5 Years in the Jorongan Health Center Work Area - Advenia Lusi Hariani (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Toddlers are individuals or groups of individuals from a population who are within a certain age range. Toddler age can be grouped into three groups, namely infant age groups (0-2 years), toddler groups (2-3 years), and preschool groups (> 3-5 years) (Chandra Juita, 2021). The purpose of this study was to analyze low birth weight with stunting in children aged 1-5 years in the working area of ​​the Jorongan Health Center.The research design used correlational analysis. The population was all children aged 1-5 years and experience LBW in February 2023 as many as 194 people. The research sample included 131 toddlers aged 1-5 years who had LBW according to the inclusion and exclusion criteria in February 2023 used the Random Sampling technique. Collecting data using a questionnaire then the data is processed using SPSS using Chi square. The results of the analysis showed that the majority of respondents who experienced LBW were 130 people (100%), the incidence of stunting was 76 people (58%). while the results of the Chi-Square test between LBW and the incidence of stunting obtained a p-value of 0.000 (p-value) (smaller than 0.05) so there was a significant relationship between the LBW variable and the incidence of One stunting of the causes of stunting in LBW children is influenced by socio-economic factors, such as education level, income, and number of household members which causes chronic nutritional problems, in the short term is disruption of brain development, intelligence, physical growth, and metabolic disorders in the body.